Analisis Metode Histogram Equalization Dalam Proses Perbaikan Gambar Closed Circuit Television (CCTV) - Manalu, Rini Elisabet (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The problem in the scope of the image is where every image we have has quality weaknesses, colors are too contrast, lack of intensity, blurring, and one of them is containing a lot of noise as is the case with CCTV images. The image recorded by CCTV has a lot of noise, so the resulting image is not very clear. Therefore we need a method to reduce noise. In minimizing this, it is necessary to improve the image that aims to get better image results than before, so that the image can be seen more clearly. Image improvement is one of the early techniques in the process. There are so many techniques used in the image enhancement process, one of which is histogram equalization. Thus, the author feels that this CCTV image improvement needs to be improved with this method, and requires SNR as a comparison of image results and timing run as a measure of the speed needed during the reduction process. Histogram equalization is changing the sharpness values ​​of the image, so that the distribution is uniform, which is obtained by changing the degree of gray of the pixels. SNR to determine the level of image quality after noise reduction, in the SNR process a comparison of the resulting image and the initial image will be carried out to find a rough estimate of image improvement. Timing run to obtain the length of time obtained during the noise reduction process in an image takes place. This study describes how to improve the image based on histogram equalization method